2018
DOI: 10.3390/w10121839
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis to Investigate the Reliability of the Grid-Based Rainfall-Runoff Model

Abstract: This study aimed to assess the suitability of the parameters of a physically based, distributed, grid-based rainfall-runoff model. We analyzed parameter sensitivity with a dataset of eight rainfall events that occurred in two catchments of South Korea, using the Sobol’ method. Parameters identified as sensitive responded adequately to the scale of the rainfall events and the objective functions employed. Parameter sensitivity varied depending on rainfall scale, even in the same catchment. Interestingly, for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…We employed the Sobol' method [31] for the sensitivity analysis of the parameters, which is a variance-based quantitative global sensitivity analysis method. The usefulness of this method was demonstrated in various studies (e.g., [32][33][34]). This method quantifies the relative contributions of the individual parameters and parameter interactions to the model output variance by the decomposition of the output variance.…”
Section: Sensitivity Analysis Methodsmentioning
confidence: 98%
“…We employed the Sobol' method [31] for the sensitivity analysis of the parameters, which is a variance-based quantitative global sensitivity analysis method. The usefulness of this method was demonstrated in various studies (e.g., [32][33][34]). This method quantifies the relative contributions of the individual parameters and parameter interactions to the model output variance by the decomposition of the output variance.…”
Section: Sensitivity Analysis Methodsmentioning
confidence: 98%
“…This analysis has been applied in different levels of watersheds. Shin and Choi [25] found that the size of the catchment makes a difference in the parameter sensitivity between rainfall events.…”
Section: Introductionmentioning
confidence: 99%
“…where X i (i = 1, 2, 3) are uniformly distributed on interval [−π, π]. (11). The definitions of the Sobol' main index and the presented measure have a similar form, thus leading to a certain relationship between them.…”
Section: Numerical Example 3: Ishigami Functionmentioning
confidence: 98%
“…Step 4: Calculate the expectation of all conditional PWMs, i.e., E X i β k X ∼i (Y|X i ) , and ω k i can be easily obtained using Equation (11). After finishing the calculation of ω k i of all variables, the normalized versions also can be evaluated in Equation (12).…”
Section: Double-loop-repeated-set Numerical Estimatorsmentioning
confidence: 99%
See 1 more Smart Citation